지속가능 에너지 패러다임 변화속에서 석탄의 활용 - 박제현(Jay Hyun Park); 양인재(In Jae Yang); 이진수(Jin Soo Lee); 이청룡(Cheong Ryong Lee) (자원환경지질, 2020)
The policy for Green New Deal will promote the shift of the application to coal as feedstock from coal as fuel. Coal can be used as fuel for production of hydrogen and as feedstock materials such as synthetic graphite or activated carbon. Hydrogen is obtained from syngas produced through Steam carbon(SC), Water-Gas Shift(WGS), and Carbonation reactions, and these processes should be used in conjunction with CO2 sequestration technology. Anthracite has a potential in terms of cost advantage as a feedstock compared to a petroleum pitch, because Synthetic graphite is prepared by heat treating an anthracite with high rank to a graphitization temperature which is in the range of 2400~2800℃, in the presence of inorganic catalyst such as silicon or iron. From several studies, it has been confirmed that coal-based activated carbon(AC) is manufactured with quality similar to the large specific surface area and much micropore volume of lignin-based AC, can be prepared. Therefore it is expected that lignin-based AC is replaced to coal-based AC. 그린뉴딜정책의 실현은 석탄을 연료에서 원료로 활용분야로의 전환을 촉진시킬 것이다. 석탄은 수소의 생산, 인조 흑연 및 활성탄의 제조 원료로 활용될 수 있다. 석탄은 Steam carbon(SC) 반응과 Water-Gas Shift(WGS) 반응 및 탄산화 반응을 통하여 수소를 생산할 수 있으며, CO2격리기술과 연동되어 사용되어야 한다. 인조흑연은 실리콘이나 철 등의 무기촉매의 존재하에서 탄화도가 높은 무연탄 등을 2400~2800℃의 흑연화 온도까지 열처리함으로서 제조될 수 있기 때문에 무연탄은 석유계 피치에 비해 원료 가격경쟁력 측면에서 잠재성이 있다. 한편, 최근 목질기원의 활성탄에 필적하는 넓은 비표면적 혹은 많은 양의 미세기공을 가진 석탄기원의 활성탄이 제조될 수 있음을 여러 연구를 통해 확인되었다. 따라서 석탄기원의 활성탄은 목질기원의 활성탄을 대체할 수 있을 것으로 기대된다.